The Effectiveness of Nesting and Lighting in Physiological Function for Low Birth Weight Babies in Sidoarjo - Kusmini Suprihatin; Yessy Dessy Arna; Siti Maemonah; Sari Luthfiyah; Alfi Maziyah (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2023)
One of the goals of the Millennium Development Goals (MDG's) is to lower infant and child mortality rates. In 2006 according to the World Health Organization (WHO) infant mortality rate in the world was 49 per1000 births and the most cause of death was Low Birth Weight Babies. In Sidoarjo Hospital the birth rate of BBLR in the last 3 months is still high ranging from 30-38 babies. This study aims to analyze the effectiveness of nesting and lighting in physiological function for LBW babies in RSUD Sidoarjo. This type of research is a quasy experiment with a nonrandomized pretest and posttest with control group design with purposive sampling in the Infant Room and NICU of Sidoarjo Hospital as many as 61 (40 control groups and 21 intervention groups). Measuring instruments used are luxmeters, heart rate meters, oximeters, thermometers and observation sheets. The independent variables are the use of light shields and nesting and the dependent variables are pulse frequency and oxygen saturation. The results showed there was a difference in value between pre and post test heart rate and oxygen saturation in the intervention group with a value of p< 0.05 and there was a difference between the control group and the intervention group in the respiration rate counts pre and post intervention, the post heart rate intervention, and the post temperature intervention with a value of p<0.05. The physiological condition of the baby is related to temperature, respiration and relatively stable heart rate and the use of nesting and light protection affects the physiological stability of the heart rate and oxygen saturation